Genetic diversity of Yeast (Saccharomyces cerevisiae) Strains by using RAPD Marker - A.S., Pawar; Kumar, Kunvar Gyanendra; Singh, R.P. (International Journal of Environment, Agriculture and Biotechnology, 2024)
The term ‘wine’ is applied to the product made by the alcoholic fermentation by yeast in which the sugars are converted into alcohol and carbon dioxide. Genetic similarity was calculated using Jaccard’s similarity coefficient and cluster analysis revealed two major clusters. The diversity at molecular level was analyzed with elucidian distance of 0.40. Out of ten wine yeast strains studied at molecular level, two strains showed maximum similarity i.e. 79 % between them viz. NCIM 3045 and 3200. Genetic diversity was analyzed based on data obtained by 11 RAPD primers. Most of the primers were found 85.71 to 100% polymorphic in nature.